AN ERROR ANALYSIS OF SIMPLE PAST TENSE IN AUTOBIOGRAPHY ESSAY: CASE IN FIFTH SEMESTER OF ENGLISH DEPARTMENT STUDENTS AT STKIP AL MAKSUM - Yunita Sari Adelina (LPPM STKIP AL MAKSUM, 2022)
This research tells about an error analysis in autobiography essay particularly focus on simple past tense. The objective of this research is to find the types of errors and the dominant factor of the errors. This research involved the qualitative method. The participant of this research is English Department students, fifth semester at STKIP Al Maksum. There were the errors of the autobiography essay writing: omission 2 or 20%, addition 2 or 20%, misinformation 4 or 40%, and misordering 2 or 20%. The dominant factor that influences the use of the simple past tense in autobiography essay is the interference of the mother tongue or mother tongue and the minor factor is over-generalization.